Rheological behavior and particle alignment of cellulose nanocrystal and its composite hydrogels during 3D printing. (1st February 2021) - Ma, Tao; Lv, Linxiang; Ouyang, Chengzheng; Hu, Xinna; Liao, Xiaojun; Song, Yi; Hu, Xiaosong
Highlights: The shear-induced orientation enhances the CNC alignment along the print direction. The optimal mass fraction of pure CNC hydrogels for 3D printing is 20 wt%. CNC-pectin (HMP/LMP) composite hydrogels have favorable print fidelity. Abstract: Cellulose nanocrystal (CNC) has tremendous potential in chemical, material, and food fields as an attractive green bioresource. We formulated viscoelastic hydrogels composed of anisotropic CNC using an extrusion-based 3D printing technology. We explored the rheological properties and printability of CNC hydrogels with different concentrations (0.5–25 wt%), and quantified the shear-induced self-assembly behavior of CNC during printing. The results showed that 20 wt% CNC hydrogels exhibited optimal print resolution and fidelity, with a high degree of orientation (72 %–73 %) of CNC alignment along the printing direction. It provides quantitative guidelines for the development of 3D printable materials with particle orientation. Furthermore, we prepared two composite hydrogels for 3D printing by blending CNC with high/low methoxy pectin (HMP/LMP). The results revealed that two hydrogels had favorable print fidelity at suitable ratios (CNC: HMP = 2:8, CNC: LMP = 10:5). This provided flexible and sustainable choices for the development of medical tissue engineering.